DAMPAK LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA DINAS KEHUTANAN PROVINSI KALIMANTAN TIMUR - ., Jayanti (PREDIKSI, 2012)
Purpose of this study to find out whether there is the environmental impact of work against employee morale on Dinas Kehutanan Provinsi Kalimantan Timur. In this study there are 2 (two) variables, and each variable there are 4 (four) indicators. Indicators of the work environment: workplace hygiene korensponden choose enough, illumination / light correspondent choose right, choose a good correspondent of noise, air circulation correspondent choose good. Indicators of morale: The employee cooperation koresponden choose good, choose the level of work discipline correspondence choose well enough, job satisfaction correspondent choose quite satisfied and attendance clerks correspondents choose never not. From these results we concluded that the impact of Â work environment has a considerable influence (well enough) on the of employee morale in Dinas Kehutanan Provinsi Kalimantan Timur.